(untitled) (Cadernos de Linguagem e Sociedade, 2024)
Professor Len Unsworth is the Research Director of Educational Semiotics in English and Literacy Pedagogy in the Institute for Learning Sciences and Teacher Education (ILSTE) at the Australian Catholic University (ACU) in Sydney. Len has been involved in educational research for over 30 years, including nine recent Australian Research Council funded projects. His key research interests include: literacy and learning in school curriculum areas; literature for children and adolescents; literacy development in the English curriculum K-12; and the pedagogic role of explicit knowledge about language and the meaning-making resources of images and image-language interaction in both paper and digital media texts, including animation and film. Prior to commencing at ACU in 2014, Len was Professor in Education at Griffith University, following earlier roles as Head of the School of Education at the University of New England and Head of the School of Development and Learning in the Faculty of Education at the University of Sydney.